Role of A-type arabidopsis response regulators in meristem maintenance and regeneration - Buechel, Sabine; Leibfried, Andrea; To, Jennifer P. C.; Zhao, Zhong; Andersen, Stig U.; Kieber, Joseph J.; Lohmann, Jan U. (European journal of cell biology, 2009)
In Arabidopsis, the network responsible for the maintenance of the shoot apical meristem (SAM) is built on a negative feedback loop involving the peptide ligand CLAVATA3 (CLV3) and the homeodomain transcription factor WUSCHEL (WUS). The local WUS/CLV3 regulatory module is linked to the organism-wide cytokinin signalling system by direct transcriptional control of A-type ARABIDOPSIS RESPONSE REGULATOR genes (ARRs) by WUS. Here we investigate two A-type ARR genes, ARR7 and ARR15, which are negative regulators of cytokinin signalling. We show that the expression of ARR7, WUS and CLV3 is dependent on cytokinin signalling. While ARR7 expression strongly responds to variations in cytokinin activity, WUS and CLV3 appeared to be much more buffered against this type of variation. As earlier studies had shown that pertubation of A-type ARR activity only causes mild effects on SAM function, we employed tissue regeneration assays as a sensitised background. Root explants pre-treated on auxin and cytokinin-rich callus-inducing medium showed severely suppressed shoot regeneration when ARR7 and ARR15 were overexpressed, whereas loss of function of these genes had a strongly promoting effect. This phenotype was even aggravated in the arr3,4,5,6,7,8,9 septuple mutant. Futhermore, loss-of A-type ARR function in arr7 and arr3,4,5,6,7,8,9 mutants strongly stimulated callus development, indicating that cell proliferation is repressed by A-type ARRs. To elucidate the mechanisms underlying the enhanced capacity of the arr3,4,5,6,7,8,9 septuple mutant to develop shoot tissue in culture, we used whole-genome expression profiling. Among the transcripts with increased abundance in arr3,4,5,6,7,8,9 inflorescence apices a strong enrichment for functions in pollen development was apparent, while the reduced transcripts showed a more heterogeneous distribution of functional categories, ranging from development to pathogen defence.